Role of social support and spouse abuse in low birth weight: A Case-control study from Puducherry, India - Yamini Marimuthu; Sonali Sarkar; Shivanand Kattimani; Yuvaraj Krishnamoorthy; Bharathnag Nagappa (Wolters Kluwer Medknow Publications, 2019)
Background: Low birth weight (LBW) is a major cause of neonatal morbidity and mortality. In addition to medical/clinical risk factors, various socio-demographic factors also have an impact on birth weight. Objective: The objective of the study is to determine the association of antenatal social support and spouse abuse during pregnancy with LBW in Urban areas of Puducherry. Materials and Methods: A community-based case-control study was conducted in Puducherry. Mothers of 100 LBW infants and normal birth weight infants in 2016 were studied. Functional Social Support Questionnaire and Index of Spouse Abuse scales were used. Conditional logistic regression for matched pair studies was done for multivariate analysis. Results: Mean (± standard deviation) age and education of the study participants was 25.6 (±3.5) and 8.28 (±3.6) years, respectively. The proportion of girl child was 59% and 43% among cases and controls, respectively. Mothers with higher perceived social support (odds ratio [OR] = 0.5; 95% confidence interval [CI]: 0.4-0.7) had lesser odds of LBW. The odds of LBW was 3.6 (adjusted OR [aOR] = 3.6; 95% CI: 1.3-9.9) times and 6.9 (aOR = 6.9; 95% CI: 1.5-31.9) times greater among mothers who experienced nonphysical abuse and had pregnancy-induced hypertension respectively and it was statistically significant after adjusting for child's gender, social support, and parity. Conclusions: The presence of nonphysical abuse during the antenatal period increased the risk of LBW. The awareness should be created in the community to prevent maternal exposure to abuse.